Assessing surface and subsurface transport of neonicotinoid insecticides from no‐till crop fields. Issue 2 (2nd March 2021) - Frame, Sarah T.; Pearsons, Kirsten A.; Elkin, Kyle R.; Saporito, Louis S.; Preisendanz, Heather E.; Karsten, Heather D.; Tooker, John F.
Abstract: Increased use of neonicotinoid‐coated crop seeds introduces greater amounts of insecticides into the environment, where they are vulnerable to transport. To understand the transport of neonicotinoids from agricultural fields, we planted maize ( Zea mays L.) seeds coated with thiamethoxam in lysimeter plots in central Pennsylvania. Over the next year, we sampled water generated by rainfall and snowmelt and analyzed these samples with mass spectrometry for the neonicotinoids thiamethoxam and clothianidin (metabolite), which originated from the coated seeds. For surface and subsurface transport, thiamethoxam exhibited "first‐flush" dynamics, with concentrations highest during the first events following planting and generally decreasing for the remainder of the study. The metabolite clothianidin, however, persisted throughout the study. The mass of thiamethoxam and clothianidin exported during the study period accounted for 1.09% of the mass applied, with more than 90% of the mass transported in subsurface flow and less than 10% in surface runoff. These results suggest that surface runoff, at least for our site, is a relatively small contributor to the overall fate and transport of these insecticides and that the delivery ratio (i.e., mass exported/mass applied) observed for these compounds is similar to those of other trace‐level emerging contaminants known to negatively influence aquatic ecosystems. Core Ideas: Neonicotinoids are water‐soluble insecticides that are commonly coated on crop seeds. These insecticides are known to leech from crop fields via surface and subsurface water flow. For one year we quantified the amounts of neonicotinoids that left no‐till maize plots. The parent compound exhibited first flush dynamics, whereas the metabolite persisted longer. Our data provide insight into how neonics leave fields, better defining the risks they pose.